ISSUES OF CIVIL-LEGAL REGULATION AND CIVIL CIRCULATION OF INFORMATION - A. Ismanzhanov (Russian Journal of Economics and Law)
The article views the issues of civil-legal regulation of information and the connected with it issue of ensuring of the civil circulation of information, as well as the means of regulation of those issues.